Ferrocenylmethyl-functionalized 5-membered heterocycles: Synthesis, solid-state structure and electrochemical investigations. (15th September 2018) - Taher, Deeb; Ghazzy, Asma; Awwadi, Firas F.; Helal, Wissam; Al Khalyfeh, Khaled; Korb, Marcus; Hildebrandt, Alexander; Kovalski, Eduard; Lang, Heinrich
Graphical abstract: The synthesis of Fe( η 5 -C5 H4 CH2 OC(O)R)2 and 2, 5-(FcCH2 OC(O))2 - c C4 H2 X (X = 5-membered heterocycle) is discussed. The molecular solid state structures of three compounds are reported. Electrochemical investigations show reversible Fc/Fc + redox events. DFT calculations reveal different HOMO–LUMO gaps depending on the nature of the heterocyclic ring. Abstract: Treatment of Fe( η 5 -C5 H4 CH2 OH)2 (1 ) with two equivalents of ClC(O)R (2 ) (a, R = 2- c C4 H3 O; b, R = 2- c C4 H3 S; c, R = 2- c C4 H3 Se; d, R = 3- c C4 H3 S) produced the corresponding ferrocenylmethyl carboxylates Fe( η 5 -C5 H4 CH2 OC(O)R)2 (3a –d ), while the reaction of FcCH2 OLi (Fc = Fe( η 5 -C5 H5 )( η 5 -C5 H4 )) with 2, 5-(ClC(O))2 - c C4 H2 X (5 ) (a, X = O; b, X = S; c, X = Se) in a 2:1 molar ratio gave 2, 5-(FcCH2 OC(O))2 - c C4 H2 X (6a –c ). Compounds 3a –d and 6a –c were characterized by elemental analysis, NMR ( 1 H and 13 C{ 1 H}) and IR spectroscopy. The molecular structures of 3a, b, d in the solid state were determined by single crystal X-ray structure analysis. Compound 3a crystallizes in the monoclinic space group P 21 / c, while 3b, d crystallize in the triclinic space group P - 1 ¯ . The ester groups and the heteroatoms are in an anti arrangement with respect to each other. Cyclic voltammetry measurements for 3a –d and 6a –c show reversible electrochemical processes (Fc/Fc + ) between 165 and 176 mV for 3a –d, and 94 and 116 mV for 6a –cb, using [N n Bu4 ][B(C6 F5 )4 ] as the supporting electrolyte. It was found that for 3a, a somewhat higher Fc/Fc + redox potential ( E 0′ ) is observed when compared with the more electron-rich systems 3b, c, d . The molecular electronic structures of the title compounds were additionally investigated by DFT calculations, revealing different degrees of HOMO–LUMO energy gaps within the series, due to a lowering of the LUMO energy, depending on the nature of the heterocyclic ring.